Philosophical hermeneutics and the Analects: The paradigm of tradition - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 1984)
Hermeneutics, as a philosophical enterprise, is not new; it can be traced back at least to Friedrich Schleiermacher (1768-1834) and Wilhelm Dilthey (1833-1911).1 Yet hermeneutics did not reach its philosophical maturity and acquire the worldwide recognition that it deserves until Hans-Georg Gadamer published his magnum opus, Truth and Method, in 1960.2 Here, with the help of Heidegger, hermeneutics is transformed from a general methodology of the "human sciences" (Geisteswissenschaften) into a full-fledged "practical" philo- sophy.3 With Gadamer, as we shall see, hermeneutics can no longer be under- stood as merely a theory of interpretation; rather, it is to be seen as an attempt to disclose the ontological dimension of understanding as a mode of being of our being-in-the-world. It is on this fundamental philosophical level that I see a possible dialogue between hermeneutics and Confucian thought emerging. More precisely, it seems to me that Gadamer's hermeneutics and the Analects can be fruitfully compared in terms of their general "practical" orientation and their specific emphasis on the notion of "tradition." This is the central claim which we will try to explicate in the following pages. As Gadamer is often misunderstood and the term "hermeneutics" is now used in diverse contexts, we will begin with a fairly detailed outline of Gadamer's understanding of "tradition" and of hermeneutics as a practical philosophy. Then, using a Gadamerian framework, the notion of tradition in the Analects will be examined. In the final section, we will very briefly sketch out the paradigm of tradition that emerges, with the view of a possible contribution to the general problematic of an East-West philosophical dialogue.